Pemanfaatan Biopori dan Rainwater harvesting guna Mereduksi Tinggi Banjir (Studi Kasus: Permuahan PGRI Balikpapan) - Rossana Margareth Kadar Yanti; Andika Ade Indra Saputra; Muhammad Hadid (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Flood is a disaster which is impact of the land use changing from land for rainwater absorption to resident area or others. Rainwater has a high potential that can be used by people. Every stakeholder, especially residents, can take participation in flood prevention. Methods that can be used by the community in anticipating or reducing the impact of floods are the bio-pore and rainwater harvesting. This community service activity aims to provide information and training on the use of bio-pore and harvesting rainwater to reduce the risk of flooding. The counseling was conducted on RT 10 Blok K Housing PGRI Graha Indah Balikpapan residents. This activity involves the community implementing bio-pore in residential areas and working together to install rainwater reservoirs in residential mosques to be used as a water source for ablution.